A aplicação de sanções pelo Município aos bens imóveis de titularidade dos Estados e da União Federal em razão do descumprimento da Função Social da Propriedade - Leão, Raisa Reis (2019)
The Federal Constitution in its article 182, paragraph 2 determines that the property will fulfill its social function when it meets the requirements expressed in the Master Plan. In an initial analysis of the constitutional text, it could be understood that the constituent merely intended to regulate the properties owned by private individuals and would inevitably incur the chaotic and discriminatory situation of making the public good immune to the master plan and the appropriate urban planning of the cities. The Federal Constitution of 1988 brought, among its fundamental individual rights and guarantees, an inseparable link between property and its social function (art. 5, item. XXII and XXIII). The Social Function of Property is no longer simply a matter of imposing negative limits on the Right to Property, that means that it is no longer enough for the owner to avoid causing harm to others by exercising his Rights, the owner needs, furthermore, may use it in a way that contributes to social development, under penalty even of the loss of his property. In this context, it is necessary to rethink not only private property, based on the principle of social function, as already recognized. It is necessary to revisit the concept of public property, often understood as “public administration” property in a strict and antagonistic sense to the social function of these properties for the city and often to the collective interest. Mere public dominance does not guarantee compliance with the principle of the social function of property, which depends on the effective destination and use of these properties as precepts that meet the public interest and perform a fair and sustainable urban order. Throughout the present work, it will be recognized the incidence of the social function principle to the urban public property and will verify the possibility of the Municipality to apply the sanctions according to the Federal Constitution and ordinary legislation, namely: compulsory installment, building or use; the time-progressive urban property tax; the expropriation with payment through public debt securities previously approved by the Federal Senate, with redemption term of up to ten years, when the property that violates the principle of the social function of property, belongs to the States and / or the Federal Union